A Study of Linguistic Features Of Personification In English and Vietnamese Love Songs - Phạm Thị Phú Thương; Ho Thi Kieu Oanh Ph.D huong dan (2012)
Introduction; Literature review and theoretical background; Methods and procedures...
Master thesis in the English language.
Keywords: Phạm Thị Phú Thương,2012, Linguistic,Features, Love Songs